2020
DOI: 10.2147/cmar.s261894
|View full text |Cite
|
Sign up to set email alerts
|

<p>Kinesin Superfamily Member 18B (KIF18B) Promotes Cell Proliferation in Colon Adenocarcinoma</p>

Abstract: Background The role of kinesin superfamily proteins (KIFs) has been reported in a variety of tumors and KIFs contributed to the proliferation of cancer cells. But few studies were focus on colon adenocarcinoma. Methods Through bioinformatics analysis and immunohistochemistry (IHC) assays, the expression of KIF18B in colon adenocarcinoma tissues was determined. Stable KIF18B-depleted cell lines were constructed using lentivirus-mediated shRNA of KIF18B. Cell colony forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Excessive proliferation of cells is closely related to the occurrence of tumors (Shi et al, 2020). Zhao et al (2020) found that the KIF18B promotes cell proliferation in colon adenocarcinoma and tumor growth in vitro and in vivo. In our research, we found that the ability and speed of CRC cells proliferation were slower in the KIFC3-depleted groups in the EdU assay, CCK-8 and colony formation assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive proliferation of cells is closely related to the occurrence of tumors (Shi et al, 2020). Zhao et al (2020) found that the KIF18B promotes cell proliferation in colon adenocarcinoma and tumor growth in vitro and in vivo. In our research, we found that the ability and speed of CRC cells proliferation were slower in the KIFC3-depleted groups in the EdU assay, CCK-8 and colony formation assay.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting daughter cells may exhibit cancerous behavior, including the ability of increased metastasis ( Almeida and Maiato, 2018 ; Lucanus and Yip, 2018 ). The invasion and migration of tumors are the main reasons leading to the failure of tumor treatment and poor prognosis, which cause low 5-year survival rates ( Zhan et al, 2020 ; Zhao et al, 2020 ). In tumorigenesis and metastasis, EMT plays a critical role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated KIFs were involved in different types of cancers [ 5 ]. For example, KIF15 can promote cancer stem cell phenotype in hepatocellular carcinoma [ 10 ], while KIF18B can promote cell proliferation in hepatocellular carcinoma [ 11 ]. In addition, several studies have illustrated KIF23 participates in the occurrence of multiple cancers, including gastric cancer, bladder cancer, lung cancer and pancreatic ductal adenocarcinoma [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kinesin superfamily proteins (also known as KIFs) are important molecular motors that directionally transport various cargos, including membranous organelles, protein complexes and mRNAs [7] . The mechanisms how different kinesins recognize and bind to speci c cargos, as well as how determine the direction of transport and kinesins unload cargo, have already been revealed [8][9][10] . And KIFs also play an important role in the process of tumor proliferation, invasion and metastasis.Li et al reported KIF2C/4A/10/11/14/18B/20A/23 predict poor prognosis and promote cell proliferation in hepatocellular carcinoma [11] .…”
Section: Introductionmentioning
confidence: 99%